Picture book reading on the development of preschoolers in rural areas of China: Effects on language, inhibition, and theory of mind - Zheng, Yuanxia; Li, Danyang; Chen, Zhongqi; Liu, Guoxiong (Frontiers in Psychology, 2022)
Studies have shown that book reading intervention may scaffold children’s language development. However, whether book reading interventions are equally effective for children’s cognitive development in Chinese rural school setting remain to be explored. We conducted a four-month book reading intervention to address these issues in rural Chinese areas. Three hundred twenty-one children aged between 2.56 and 6.47 ages (M = 4.66 ages, SD = 0.80) were assigned to 3 groups: (a) control group without donated picture books, (b) active reading control group with donated picture books, (c) intervention group with 4-month instructed picture book reading intervention. The findings indicated that the available books could produce significant positive changes in the development of receptive language (F (1, 191) = 14.46, p < .01) and inhibitory control (F (1,190) = 7.64, p = .01) of rural children. However, a 4-month intervention was noneffective at boosting participants’ performance on these tasks (F (1, 203) = 0.07 2.73, p > .10). Results discussed the possible explanations, implications for behavioral intervention researchers and suggestions for social service organizations or public institutions.